PENTINGNYA MENJAGA KEHARMONISAN DAN KESEHATAN PADA ERA NEW NORMAL - Renny Christiarini; Amanda Rosetia; Nur Hidayati; Jason Jerico; Willy Antonio; Joy Celyn; Estefan Estefan; Try Monica; Andi Andi; Shintia Dewi; Fibiyani Fibiyani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2020)
Covid-19 is a new type of virus that has hit countries around the world. Therefore, to combat this pandemic, it is health workers who have a major role in combating the spread of this virus. So this review was conducted to sensitize the public to help health workers in maintaining personal health and encouragement to eliminate negative views for health workers by interviewing and distributing questionnaires to collect data, which will then be processed and will be presented in the form of videos as a result of the project. Through the video will contain true, proper, and important information with moving animation which can attract everyone's attention. Through this video, people will know the importance of self-awareness on health that will have an impact on those around them and health workers at the time of this Covid-19 pandemic.